2001
DOI: 10.1063/1.1340558
|View full text |Cite
|
Sign up to set email alerts
|

Use of a multiwavelength pyrometer in several elevated temperature aerospace applications

Abstract: A multiwavelength pyrometer was developed for applications unique to aerospace environments. It was shown to be a useful and versatile technique for measuring temperature, even when the emissivity is unknown. It has also been used to measure the surface temperatures of ceramic zircornia thermal barrier coatings and alumina. The close agreement between pyrometer and thin film thermocouple temperatures provided an independent check. Other applications of the multiwavelength pyrometer are simultaneous surface and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(32 citation statements)
references
References 8 publications
(4 reference statements)
1
31
0
Order By: Relevance
“…Considering the three conditions of particles that can exist in the spray stream -solid, partially molten and fully moltenthe radiated intensity as detected by the pyrometer is dependent on the optical properties of solid and liquid zirconia. In previously published research paper, Ng et al (40) have analyzed and presented results of the case of multi-wavelength pyrometry applied to optically transparent materials. They have demonstrated that when the principle is implemented by acquiring the spectrum over a large range of wavelengths, it is possible to distinguish the contribution from the surface and from the bulk of a transparent material.…”
Section: Variations In Particle Distributions Through the Complete Prmentioning
confidence: 98%
“…Considering the three conditions of particles that can exist in the spray stream -solid, partially molten and fully moltenthe radiated intensity as detected by the pyrometer is dependent on the optical properties of solid and liquid zirconia. In previously published research paper, Ng et al (40) have analyzed and presented results of the case of multi-wavelength pyrometry applied to optically transparent materials. They have demonstrated that when the principle is implemented by acquiring the spectrum over a large range of wavelengths, it is possible to distinguish the contribution from the surface and from the bulk of a transparent material.…”
Section: Variations In Particle Distributions Through the Complete Prmentioning
confidence: 98%
“…Previous studies were devoted either to emissivity determination of ceramic samples under isothermal conditions [11][12][13][14] or to accurate prediction of temperature distributions in ceramics [15,16]. The present research is a contribution to characterizations of non-isothermal TBCs for mean temperatures higher than 1000 • C. The main objective is to determine the infrared radiative emission of ceramic samples under realistic thermal boundary conditions that correspond to samples submitted to high heat flux on one side only.…”
Section: Introductionmentioning
confidence: 98%
“…In the study of radiation pyrometry theories and technologies, the complexity and uncertainty of actual object spectrum emissivity and the calibration problem caused by the temperature field measurement are always the key obstacles for accurate temperature measurement. Thus many radiation pyrometry methods and technologies arose [2][3][4][5][6][7][8][9][10][11][12][13] . However, our preliminary study put forward the primary spectrum pyrometry [14][15][16] based on the waveband measurement, the emissivity model in the narrow waveband and the normalization processing, and realized the true temperature field measurement without the calibrations of emissivity and spatial geometry.…”
mentioning
confidence: 99%